Enhancing mathematical literacy: A comparative study of mathematics learning curricula in Thailand and Indonesia - Fauzan, Ahmad; Harisman, Yulyanti; Boriboon, Gumpanat; Syaputra, Hamdani; Hafizatunnisa, Hafizatunnisa (Jurnal Infinity, 2025)
PISA studies from 2000 to 2022 revealed that the achievements of Thailand’s students in mathematics were always better than those of Indonesian students. Thailand still uses the 2008 curriculum until now. Meanwhile, Indonesia already changed its curriculum three times during these periods, namely Curriculum 2006, Curriculum 2013, and Curriculum 2020. Based on this data, it is important to investigate the impact of the curriculum and its implementation on students’ mathematical literacy. This study aimed to investigate how students in Thailand performed better in mathematical literacy compared to their Indonesian counterparts within the context of mathematics curricula.  We compared the mathematics curricula of the two countries and analyzed the implementation of the curricula in mathematics learning. Document analysis, observations, and interviews were conducted. The results show that the curricula and how they are implemented in the two countries are not strikingly different. Three notable differences are students’ focus in the learning process, the preparation of learning admissions by teachers, and changes in the curriculum.